Factors Related to Schoold Food Snacks (SFS) Safety Through the Test of Borax, Formalin, and Escherichia coliBacteria (Public Health Perspective Journal, 2018)
Food safety of primary school children snack is a source of health problems that must be considered. In 2010, BPOM reported 141 cases of food poisoning caused by School Food Snacks (SFS) with 79% occurred at the primary school level. The purpose of this research is to analyze factors related to food safety of school children in elementary school in Salatiga city. Type of observational analytic research using cross sectional design. The sampling technique used is the total sampling number of 35 respondents based on the inclusion and exclusion criteria. The research instrument using aquestionaire and examination of food samples of meatballs. Analysis using chi square. The results showed that sellers' knowledge, pedagogical education and hygiene of food snacks were factors related to School Food Snacks (SFS)safety through the test of borax, formalin and eschercia coli bacteria at Salatiga primary school (p 0.05). The selling age and duration of selling are not factors related to School Food Snacks (SFS) safety through the test of borax, formalin and eschercia coli bacteria at Salatiga Elementary School (p 0,05). Suggestions that can be recommended by researchers is the need to improve the policy, planning and the role of Education Office and Public Health Service in improving food safety of snack in Salatiga primary school.